2009
DOI: 10.3350/kjhep.2009.15.s6.s29
|View full text |Cite
|
Sign up to set email alerts
|

Current status of liver diseases in Korea: Toxic and alcoholic liver diseases

Abstract: The study of the epidemiology of toxic liver injury has been limited in Korea. The number of hospitalizations for toxic liver injury has been estimated to be 2,400 persons per year. About 30~40% of fulminant hepatitis was attributed to toxic hepatitis. The frequent causative agents of toxic hepatitis in Korea are herbal medicines (34-40%), folk remedies (23-34%), and prescribed medicines (24-55%). However, the most common agents causing severe liver injury including fulminant hepatitis are herbal medicine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…A high propensity toward combined alcohol and nicotine use was observed in Korean adults; this result is similar to the results from other population-based studies that independently found a significant association between alcohol use disorder and smoking (Hasin, Stinson, Ogburn, & Grant, 2007;Kim et al, 2009). Codependence on alcohol and nicotine is the most common cause of preventable morbidity and mortality in the world (Ait-Daoud et al, 2005;Bien & Burge, 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A high propensity toward combined alcohol and nicotine use was observed in Korean adults; this result is similar to the results from other population-based studies that independently found a significant association between alcohol use disorder and smoking (Hasin, Stinson, Ogburn, & Grant, 2007;Kim et al, 2009). Codependence on alcohol and nicotine is the most common cause of preventable morbidity and mortality in the world (Ait-Daoud et al, 2005;Bien & Burge, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the recent interest in viral hepatitis-induced liver disease, alcohol consumption continues to be a common cause of acute and chronic liver disease (Kim, 2009;Savolainen, Liesto, Mannikko, Penttila, & Karhunen, 1993). ALD encompasses a spectrum of injury, ranging from minimal abnormalities of hepatic steatosis to more significant signs and symptoms of liver disease related to inflammation or frank advanced fibrosis, or both; however, individuals with ALD may be entirely asymptomatic (Levitsky & Mailliard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vesivirus in environmental reservoirs include infected wild animals, food animals (swine, cattle), fin‐fish, and aquatic filter feeders such as mussels, clams and oysters, which can concentrate virus from the water [Smith et al, 1998b; Smith, 2000; Terio et al, 2010; Westrell et al, 2010]. Liver function may also be affected by Korean food, alcohol consumption, and traditional, medicine and these may exacerbate liver disease [Kim, 2009]. Therefore, the Korean people may be more susceptible to symptomatic Vesivirus infections and if so, data reported above may reflect a culturally associated increase in vesiviral liver disease among Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, 7-31% of chronic liver diseases are alcoholic liver diseases 3,4. Nevertheless, because drinking rates are substantial in chronic hepatitis B and hepatitis C patients, more patients than expected may be affected by alcohol.…”
Section: Introductionmentioning
confidence: 99%